Effect of paclobutrazol on growth and root morphology of 12 crossed stevia in Vitro - Qurrota Aini; Noladhi Wicaksana; Suseno Amien (Universitas Padjadjaran, 2022)
AbstractStevia (Stevia rebaudiana Bertoni) is a low-calorie alternative sweetener. The superior varieties of Stevia in Indonesia are limited. Availability of seeds plays an important role in the Stevia plant breeding program for both the selection stage and the production of high-yielding varieties. Tissue culture is the best method of Stevia propagation, but the low adaptability of plantlets causes death in the acclimatization phase. The growth and root morphology of 12 crossbreed Stevia were evaluated. A Completely Randomized Design was used with factorial consisting of two factors were Stevia genotypes (STG1,7,8,10, SBG3,4,5,7,10, SGB2,3, and SBT11) and the plant growth regulator (PGR) concentration of Paclobutrazol (PBZ) (0.1, 0.5, and 1.0 ppm) and indole acetic acid (IAA) control (0.5 and 1 ppm). The results showed that the fastest shoot emergence time was SBT11 at 0.1 and 0.5 ppm PBZ media at 4 days after culture (DAC). The fastest root emergence time was SBG7 at 0.1 and 1 ppm PBZ media (8 DAC). The highest shoots were at 1 ppm IAA media (18 cm). The highest number of shoots was STG10 at 1 ppm PBZ and SBG3 at 0.5 ppm IAA (4 shoots). The highest number of internodes was SBG5 at 0.5 ppm IAA (25 internodes). The highest number of leaves was SBG3 at 0.5 ppm IAA (57 leaves). The highest number of roots was SGB2 at 0.5 ppm PBZ (5 roots). The greenest leaf color was SBG7 at 1 ppm PBZ media. The PBZ accelerated the emergence of shoots and roots and the number of roots.Keywords: Genotype, Interaction, in vitro, Paclobutrazol, Stevia. AbstrakStevia (Stevia rebaudiana Bertoni) merupakan sumber pemanis alternatif berkalori rendah. Varietas unggul Stevia di Indonesia terbatas. Ketersediaan bibit menjadi kunci dalam program pemuliaan tanaman Stevia baik untuk pada tahap seleksi maupun produksi varietas unggul. Kultur jaringan adalah metode perbanyakan Stevia terbaik, tetapi kemampuan adaptasi planlet yang rendah menyebabkan kematian pada fase aklimatisasi. Tujuan penelitian ini untuk mengevaluasi pertumbuhan dan morfologi akar dari 12 Stevia hasil persilangan. Metode percobaan yang digunakan adalah Rancangan Acak Lengkap faktorial dua faktor, yaitu genotipe Stevia (STG1,7,8,10, SBG3,4,5,7,10, SGB2,3, and SBT11) dan konsentrasi zat pengatur tumbuh paklobutrazol (PBZ) (0,1; 0,5; dan 1,0 ppm) serta indole acetic acid (IAA) sebagai kontrol (0,5 dan 1 ppm). Hasil penelitian menunjukkan waktu muncul tunas tercepat adalah SBT11 pada 0,1 dan 0,5 ppm PBZ pada 4 hari setelah tanam (HST). Waktu muncul akar tercepat adalah SBG7 pada 0,1 dan 1 ppm PBZ (8 HST). Tunas tertinggi diperoleh pada media 1 ppm IAA (18 cm). Jumlah tunas terbanyak diperoleh STG10 pada 1 ppm PBZ dan SBG3 pada 0,5 ppm IAA (4 tunas). Jumlah ruas terbanyak diperoleh SBG5 pada 0,5 ppm IAA (25 ruas). Jumlah daun terbanyak diperoleh SBG3 pada 0,5 ppm IAA (57 daun). Jumlah akar terbanyak diperoleh SGB2 pada 0,5 ppm PBZ (5 akar). Warna daun terhijau diperoleh SBG7 pada 1 ppm PBZ.Kata Kunci: Genotipe, Interaksi, in vitro, Paclobutrazol, Stevia.